(untitled) (Bangladesh Journal of Endosurgery, 2014)
Background: Endoscopic retrograde cholangiopancreatography (ERCP) is a universally established modality in the evaluation and treatment of adults with suspected biliary and pancreatic disease. Experience with ERCP in children has been relatively limited especially in a developing country like Bangladesh. Objective: Aim of this study is to evaluate the diagnostic and therapeutic yields of ERCP for biliary and pancreatic diseases in Bangladeshi children. Design and settings: This retrospective study was conducted in the departments of Gastroenterology & Hepatology of Bangabandhu Memorial Hospital and Chattagram Metropolitan Hospital, Chittagong, Bangladesh between 2004 and 2013. Patients: Seventy-three patients (14 males and 59 females) aged 1 year 7 months to 18 years with the suspicion of biliary or pancreatic diseases were included in this study. Interventions: Seventy-six procedures of ERCPs were performed. Main outcome measures: Common indications for ERCP and its therapeutic outcomes were assessed. Results: The most common indications were biliary ascariasis (25), choledocholithiasis (17), biliary dilatation of unknown cause (11), chronic pancreatitis (3), choledochal cyst (1), and Mirizzi syndrome (1). Therapeutic procedures included sphincterotomy (41), worm extraction (25), stone extraction (12), and biliary stenting (2). Adverse events were uncommon and usually minor. Conclusion: ERCP is a highly effective and safe diagnostic and therapeutic modality with highest indication for biliary ascariasis in Bangladeshi children. DOI: http://dx.doi.org/10.11593/bje.2013.0103.0019 Bangladesh Journal of Endosurgery Vol.1(3) September 2013: 9-12